A Morphosyntactic Analysis Of The Clause Structure Of The Endangered Mehri Language In Yemen - Al-Qumair, Saeed Saad Njdan (2017)
This study investigates synchronically the morphological and syntactic features of the Mehri language that is spoken by Mehri people who originally live in Al-Mahrah governorate at the eastern part of Yemen. It focuses on the variety of Šḥān territory as the one which is not influenced by Arabic. Generally, Mehri belongs to the Modern South Arabian Languages [henceforth, MSAL]. This group descends from Semitic family that itself is affiliated to a wider group called Afro-Asiatic family. Though Mehri is considered to be an endangered language due to the influence of Arabic, it has yet been studied or documented properly.